(untitled) (AYUSHDHARA, 2023)
The literal translations of the terms "Rasa" and "Ayana" are "Dhatu" and "Path," respectively. Hence, Rasayana refers to Rasa and its motion inside the body. Rasayana’s role in the body is to nourish each cell and tissue. Ahara Rasa serves as the raw ingredient. Stanya, the Prasada baga of Madhura rasa and Rasa dhatu, is created during the digestion of food. Ideal milk must have normal Prakrthi Varna, Gandha, Rasa, and Sparsha entirely dissolved in water due to its watery nature. Acharya Charaka asserts that Godughdha has 10 Gunas, which are similar to the Gunas of Ojas. Ojas, a crucial Dhatu in our bodies, enlarges as a result of this. Go ksheera is referred to as Shrestha Rasayana because it is the finest Jeevaniya Padartha. Goksheera is regarded as the best Rasayana dravya since it may be used by individuals of all ages as a part of a healthy diet and as a dietary supplement. Ghrita is composed of the following elements: Pitta-nilaharam, Rasa, Shukra, and Ojo Hitam; Niravapanam; Mrdukaram; Swaravarna Prasadanam; Kapha Medo Vivardhanam; Smruthi Budhi vardhakam; and Agni vardhakam as per Acharya Charaka. Rasayana Dravya can be appropriately ingested to encourage the normal growth and expansion of Sapta Dhatu, which in turn raises Ojas. Ojas are raised as a result of the regeneration of biological tissues and cells. It is common knowledge that the developing world has a higher risk of infectious diseases due to increased pollution, bad lifestyle choices, fast food consumption, unhygienic living conditions, and improper eating habits. In the present study, we will collect the scientific facts to re-establish the statement ‘Ksheeraghrtaabhyaso Rasayananaam’ to know the effects of regular intake of ghee and milk in the diet for rejuvenation and longevity of life.